Creativity and follow-up in the perception of the son of Agile Kairouani through his two books The Mayor and the cutters of gold - NEKBIL, Abdelaziz (Journal of Human Sciences, 2020)
The issue of literary creativity occupied the minds of Arab critics, both advanced and late, because of its profound impact on the completion of the quality of poetry.This research is concerned with the study of the issue of thefts (take)in Arabic poetry with the critic IbnRashiq al-Qayrawani (d.456 AH )Through his two books:“alomda”and “alkoradha”,which are unique in their understanding of this issue, which is considered the essence of poetic creativity.